2020
DOI: 10.1038/s41598-020-64127-9
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of a silver-microfibrillated cellulose biocomposite against susceptible and resistant bacteria

Abstract: Antibiotic Microbial Resistance (AMR) is a major global challenge as it constitutes a severe threat to global public health if not addressed. To fight against AMR bacteria, new antimicrobial agents are continually needed, and their efficacy must be tested. Historically, many transition metals have been employed, but their cytotoxicity is an issue and hence must be reduced, typically by combination with organic polymers. Cellulose of natural origin, especially those derived from unavoidable residues in the food… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 60 publications
1
24
0
Order By: Relevance
“…Despite taking a backstage role after the advent of antibiotics, silver has been continuously used in different forms [1,2]. Furthermore, due to the multidrug resistance crisis, the utilization of silver as a component of combination therapies or other novel formulations has regained interest [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Despite taking a backstage role after the advent of antibiotics, silver has been continuously used in different forms [1,2]. Furthermore, due to the multidrug resistance crisis, the utilization of silver as a component of combination therapies or other novel formulations has regained interest [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…A novel silver-microfibrillated cellulose biocomposite has been synthesized, and its antimicrobial activity was determined against relevant clinical strains. The results showed that this biocomposite has antimicrobial activity against Gram-negative and Gram-positive bacteria so that it could be applied in the development of biocompatible biomedical devices Garza-Cervantes et al, 2020a). Another promising approach toward the development of new antimicrobial combinatorial treatments is the use of transition metals, since they exhibit rapid and significant toxicity, at low concentrations, in different bacterial strains.…”
Section: Metal Nanoparticle-based Combinatorial Treatmentsmentioning
confidence: 99%
“…Cellulose can also be removed from orange peel by microwave hydrothermal treatment. Thereafter, bactericide material can be produced by incorporating silver nanoparticles into the structure, showing strong activity against Gram‐positive and Gram‐negative bacteria [232] …”
Section: Fruits and Nuts As Potential Brazilian Renewable Sourcesmentioning
confidence: 99%